Equilibrium and Thermodynamic Study of Malachite Green & Phenol Red Dyes Adsorption from Aqueous Solution by Use Algae Biomass - Ahmed Mohammed Abbas (Journal of Global Pharma Technology, 2019)
Recently the focus has been on using the surfaces of the adsorbent economically cheaper and technologically more efficient technology in treatment environmental pollution problems the biomass of Algae was applied for the adsorption of Malachite Green (MG) and Phenol Red (PhR) dyes from aqueous solution. The prepared adsorbent was characterized by FT-IR and SEM Technique .The adsorption of (MG) and (PhR) dyes onto algae biomass from aqueous phase were taken as a function of the absorbed weight, dye concentration, temperature and contact time. . The equilibrium data of (MG and PhR) adsorption onto biomass of Algae was analyzed by different isotherms models and it follows Langmuir adsorption isotherm model for the (MG) dye while (PhR) dye it follows the Freundlich isotherm. The evaluation of thermodynamics functions such as the Gibbs free energy negative for (MG) dye adsorption, positive for (PhR) dye adsorption and positive enthalpy values indicated respectively the different spontaneous and endothermic behavior of the reaction and the chemisorption of the sorption process.Keyword: Biomass, Algae, Adsorption, Malachite Green, Phenol Red.